Enkwazini, an Iron Age site on the Zululand coast - Hall, M. (Southern African Humanities, 2021)
The excavation of the Enkwazini Iron Age site, located on the Zululand coastal plain, is described. Early Iron Age ceramics, which have been dated to the fourth century A.D., are described. Molluscan faunal remains, attributable to the reoccupation of the site in the Late Iron Age, are analysed using a technique developed for fragmentary specimens. To cite this article: Hall, M. 1980. Enkwazini, an Iron Age site on the Zululand coast. Annals of the Natal Museum 24 (1): 97-109.